2011
DOI: 10.1155/2011/812135
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Three‐Dimensional Collagen‐Scaffolds Seeded with Myoblasts to Repair Skeletal Muscle Defects

Abstract: Three-dimensional (3D) engineered tissue constructs are a novel and promising approach to tissue repair and regeneration. 3D tissue constructs have the ability to restore form and function to damaged soft tissue unlike previous methods, such as plastic surgery, which are able to restore only form, leaving the function of the soft tissue often compromised. In this study, we seeded murine myoblasts (C2C12) into a collagen composite scaffold and cultured the scaffold in a roller bottle cell culture system in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…It has been reported that myoblasts have the morphological and functional capacity to regenerate muscle [35,36]. Although myoblasts cannot directly participate in neovascularization, the paracrine signaling effects of myoblasts after transplantation have been reported and these secreted factors may contribute indirectly to therapeutic angiogenesis [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that myoblasts have the morphological and functional capacity to regenerate muscle [35,36]. Although myoblasts cannot directly participate in neovascularization, the paracrine signaling effects of myoblasts after transplantation have been reported and these secreted factors may contribute indirectly to therapeutic angiogenesis [37].…”
Section: Discussionmentioning
confidence: 99%
“…One of the issues associated with protein-based scaffolds is immune rejection and the onset of a foreign body response, leading to many in vivo studies being carried out in immunodeficient animal models. For example, Ma et al used a porous collagen scaffold seeded with murine myoblasts for the treatment of skeletal muscle defects, and reported that although vascularization, innervation, and the generation of myofibers were observed, successful integration of the scaffold-tissue graft was only evident in immunecompromised animals [88].…”
Section: Hydrogelsmentioning
confidence: 99%
“…These microfabricated hydrogel substrates allow for finely tuned special features, such as grooves and wells with specific placement of proteins to direct cell attachment, proliferation and fate [53,54]. Finally, gel-based scaffolds of fibrin, collagen, and other ECM proteins are seeded with MPCs in their commercially available gel form [3,17,19,46], or can be suspended into matrices with a determined pore size by cryogelation [18,55]. …”
Section: Synthetic Scaffoldsmentioning
confidence: 99%
“…Scaffold-free technologies utilize fibroblasts obtained from skeletal muscle co-cultured with muscle satellite cells to create cell monolayers that self-assemble into 3D constructs [17,19,21,26,43,44]. Our scaffoldless tissue engineered muscle constructs are unique in that they are co-cultured with engineered tendon constructs and thus are fabricated with functional tendon ends [11,19,23,45,46]. …”
mentioning
confidence: 99%